Teaching Islamic concepts electronically : hajj as an example. - Isa, Hafizuddin; Zeki, Akram M.; Hameed, Shihab A. (IIUM Press, 2011)
Information and communication technologies (ICT) have become great changes in all aspects of life nowadays. The technology developing day by day and ICT has been used widely across the world. In term of education, IT also changes the learning approach in some aspect. ICT infrastructure helps a lot in education aspect especially in the higher academy institution. This project introduces another teaching approach that using technologies. This project is about Hajj guideline for pilgrims in 3D animation. It is another method of learning after using booklet, DVD and etc.